2013
DOI: 10.1128/aac.00920-12
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Tricyclic Compounds Blocking Malaria Parasite Oocyst Development and Transmission

Abstract: Malaria is a deadly infectious disease in many tropical and subtropical countries. Previous efforts to eradicate malaria have failed, largely due to the emergence of drug-resistant parasites, insecticide-resistant mosquitoes and, in particular, the lack of drugs or vaccines to block parasite transmission. ATP-binding cassette (ABC) transporters are known to play a role in drug transport, metabolism, and resistance in many organisms, including malaria parasites. To investigate whether a Plasmodium falciparum AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…In a recent publication, Eastman et al 54 investigated the involvement of gABCG2 in drug transport and drug resistance in gametocytes. In this study, the gene for gABCG2 was also deleted, but in contrast to our findings, there was a decrease in gametocyte production following removal of gABCG2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication, Eastman et al 54 investigated the involvement of gABCG2 in drug transport and drug resistance in gametocytes. In this study, the gene for gABCG2 was also deleted, but in contrast to our findings, there was a decrease in gametocyte production following removal of gABCG2.…”
Section: Discussionmentioning
confidence: 99%
“…In this earlier study, the two gene-deletion clones analysed were derived from a single transfection, and in their discussion the authors pointed out that a secondary off-target effect responsible for the decrease in gametocyte numbers cannot be excluded. Several attempts to restore gametocyte production by complementing the gene were unsuccessful 54 . Hence, the two principal criteria for an experimental genetics analysis 55 were not met, making it difficult to reconcile the apparent discrepancies to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Using high throughput drug screening of gene knockouts in P. falciparum, Eastman et al [36] have shown recently that knockdown of PfABCG in 3D7 decreased its sensitivity to Ketotifen, a noncompetitive H1-antihistamine drug, relative to wild type parasite. Given the differential expression of PfABCG in different strains of P. falciparum (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4). Moreover, it is not clear why knockdown of PfABCG expression in 3D7 [36], which is presumably expressed only in gametocytes and not in the asexual stages of the parasite, could affect the sensitivity of the asexual stages of the parasite to ketotifen. The fact that knockdown of PfABCG in 3D7 leads to decreased sensitivity to ketotifen suggests that the protein (PfABCG) is functionally expressed in the various asexual stages of the parasite.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation